RANCANG BANGUN PERAHU NELAYAN BERTENAGA LISTRIK DENGAN SISTEM CHARGER SOLAR PANEL TRACKER SERTA PENGATUR KECEPATAN MENGGUNAKAN ARDUINO FORWARD REVERSE DAN GEARBOX UNTUK MENINGKATKAN TORSI - Nina Paramytha IS; Bima Riansyah; Agustio Alvin Fernando; Angga Riyadi (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
This study proposes the utilization of solar energy as the primary power source for fishing boats, replacing fossil fuel-powered engines that are expensive and polluting. Fishing boats commonly rely on gasoline or solar-powered engines, but the availability and cost of fuel pose challenges for riverside communities. Additionally, fossil fuel engines generate noisy sounds that disturb the marine environment and fishermen's activities. Solar energy is chosen as an alternative due to its environmentally friendly nature as a renewable energy source. The purpose of this research is to enhance the energy efficiency and operation of fishing boats, while also reducing negative impacts on the environment. By harnessing solar panels and a solar tracking system, fishing boats can efficiently generate electric power from sunlight. The outcomes of this study are expected to aid fishermen in operating more efficiently, cutting operational costs, and mitigating noise and air pollution in the marine environment.